PENGARUH PENERAPAN MODEL PEMBELAJARAN TIPE TEAM GAMES TOURNAMENT DI INTEGRASIKAN DENGAN STAD TERHADAP HASIL BELAJAR GEOGRAFI - Endang Endang; Sunarty Suly Eraku; Fitriyane Lihawa (JAMBURA GEO EDUCATION JOURNAL, 2020)
This study aims at determining the differences in student learning outcomes by involving two classes,i.e. the experimental  classes taugtt by TGT learning model integrated with the STAD learning model as well as the control class taught by the STAD learning model. This experimental research involved all students of grade XI social sciences, namely the experimental class ( XI Social Sciences 2 ) and the control class ( XI Scocial Sciences 4 ).The hypothesis testing results show that the average learnig value of the students in the experimental class is 77,43  and the average learning value in the control class is 71,95. Considering the hypothesis testing results in Î± = 0,05, it is found that tcount = 2,447 greater than ttabel =1.679. This signifies that H0 is rejected ,and the scoes of student who lerning with the TGT cooperative learning model integration with the STAD learning model are higher that students who used the STAD cooperative learning model in Geograhy learning.